2019
DOI: 10.23851/mjs.v30i1.463
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Malondialdehyde (MDA), Homocysteine (Hcy) and C- reactive protein (CRP) in sera of patients with Angina Pectoris

Abstract: Homocysteine (Hcy) has been considered as an independent risk factor for coronary artery disease (CAD Oxidative stress and free radicals are known to have important roles in the development ofAngina Pectoris. Oxidative stress is present in cardiovascular diseases (CVDs), and hyperhomocysteinemia, an independent risk factor for these diseases, may play a role in inducing production of oxygen free radicals. The aim of this study was to determine a possible relationship between blood serum Hcy levels and lipid pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The results also showed the closeness between a group of patients with atherosclerosis and workers in fast food. MDA is a product of peroxidation of polyunsaturated fatty acids that is used as a measure of oxidative damage [50].…”
Section: Resultsmentioning
confidence: 99%
“…The results also showed the closeness between a group of patients with atherosclerosis and workers in fast food. MDA is a product of peroxidation of polyunsaturated fatty acids that is used as a measure of oxidative damage [50].…”
Section: Resultsmentioning
confidence: 99%
“…ROS considered as major modulator of growth factors and an enhancer for gene expression, consequently resulting in sustained proliferation of cancer cells 66 . Scientists have shown that ROS overproduction promotes cell grow by modulating the redox status of transcriptional factors and regulatory proteins involved in cell cycle 67 . Apoptosis is well-documented physiological action related with modulation of tissue homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The increased production of TNF-α initiates the inflammatory cascade by enhancing the release of IL-1, IL-6 and IL-8 cytokines. 62,63 Scientists have revealed that the appearance of TNF-α during inflammation has relied on the stimulation of the NF-κB mechanism. The colon tissues exposed to increased TNF-α and activated NF-κB will have increased appearance of inflammatory genes, such as COX-2, lipoxygenase-2, other cytokine release, cell adhesion molecules, chemokines and iNOS.…”
Section: Discussionmentioning
confidence: 99%